Aktifitas Imunomodulator Dan Jumlah Sel Leukosit Dari Ekstrak Kulit Buah Naga Merah (Hylocereus lemairei (Hook.) Britton & Rose) Pada Mencit Putih Jantan - Havizur Rahman; Yufri Aldi; Elda Mayanti (Jurnal Farmasi Higea, 2016)
The research of immunomodulatory activity and leucocyte cell counts of white male mice has been done by using red dragon fruit peel (Hylocereus lemairei (Hook.) Britton & Rose) extracts. Animals were divided into 4 groups, which consists of only one group was given a  NaCMC supension, 2, 3, and 4 group in extract red dragon fruit peel with a dose of 10 mg/kg BB, 50 mg/kg BB dan 100 mg/kg BB. Extracts are given for 6 days orally. The result of research showed given the extract red dragon fruit peel orally  of male mice for 6 days can improve the constants and phagocytosis index, and increasing the dose 100 mg/kg BB. The activity of the red dragon fruit peel extract also increased the counts of cells and the total counts of leukocytes was significantly (P <0,05).  A dose of 100 mg/kg BB is the best dose improve the immunomodulatory activity and leukocyte cell counts.